Early diagnosis of aortic dissection in patients with chest pain: an integrative literature review (Research, Society and Development, 2021)
Introduction: Acute Aortic Dissection (AAD) is defined as a sudden rupture of the intimate layer of the aorta, exposing the underlying layer to blood flow and creating a “false lumen” parallel to the aortic wall. DAA is an extremely lethal condition that requires rapid identification to start treatment early and prevent patient death. This review aimed to describe the main clinical manifestations of AAD and present strategies for the early and efficient identification of this condition in the emergency department. Methods: An integrative review of studies published on the PubMed and Google Scholar platforms was performed with the descriptors: “aortic dissection” AND “chest pain”. 37 articles were selected, 12 were excluded and 25 studies were used in the review. Results and Discussion: For early diagnosis, in addition to analyzing signs and symptoms, complementary tests such as radiography, computed tomography, magnetic resonance imaging, echocardiography, electrocardiogram, focused cardiac ultrasound (FOCUS) and blood tests including cardiac enzymes may be useful in the investigation. Conclusion: The studies analyzed enabled the pathological understanding of AAD, as well as the presentation of efficient forms of diagnosis and treatment of the disease.